A rigid thick Miura-Ori structure driven by bistable carbon fibre-reinforced polymer cylindrical shell. (20th October 2018) - Zhang, Zheng; Ma, Weili; Wu, Helong; Wu, Huaping; Jiang, Shaofei; Chai, Guozhong
Abstract: Origami, the art of folding paper, has inspired the development of rigid foldable structures for various applications in aerospace, biomedical, and packaging applications. In order to drive and control origami structure with thick panels, a novel rigid Miura-Ori structure with bistable anti-symmetric carbon fibre reinforced polymer (CFRP) shells was proposed in this paper. Based on the membrane hinge technique, a theoretical model of the Miura-Ori structure with thick panels combined with bistable CFRP shells was established based on the principle of minimum potential energy. Bistable CFRP shells were used as the connection and driving parts of the whole structure instead of thin-walled materials or hinged structures. Finite element simulations were conducted to explore the deformations and trigger forces. The coincident boundary conditions were provided, which were the same as those used in the compression tests using the universal tensile testing machine. Experiments were conducted to validate the simulation results. The results showed that there is good agreement between the simulation and experimental results, indicating that the bistability of the origami structure is achieved under the control of the CFRP cylindrical shells.